Hawking Radiation of Spin-1 Particles from a Three-Dimensional Rotating Hairy Black Hole - Sakallı, İzzet; Övgün, Ali (Journal of Experimental and Theoretical Physics, 2015)
We study the Hawking radiation of spin-1 particles (so-called vector particles) from a three-dimensional rotating black hole with scalar hair using a Hamilton–Jacobi ansatz. Using the Proca equation in the WKB approximation, we obtain the tunneling spectrum of vector particles. We recover the standard Hawking temperature corresponding to the emission of these particles from a rotating black hole with scalar hair
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1134/S1063776115090113) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Particle and Nuclear Physics; Classical and Quantum Gravitation, Relativity Theory; Elementary Particles, Quantum Field Theory,Solid State Physics; Hawking Radiation, Rotating Hairy Black Hole, Black Holes, General Relativity